Efektivitas Sentralisasi Fiskal Zakat Melalui Baznas dalam Pembangunan Ekonomi Lokal - Muhamad Khaerunnizam; Puji Purnawan (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
Zakat is a vital instrument in the Islamic fiscal system that plays a role in wealth redistribution and poverty alleviation. In Indonesia, zakat management is focused centrally through the National Amil Zakat Agency (BAZNAS) as the official state institution. This article aims to analyze the effectiveness of the fiscal centralization model of zakat through BAZNAS in supporting local economic development. The research uses a descriptive qualitative approach with case studies on economic empowerment programs at the district/city level. The results show that the centralization model provides advantages in the form of standardization of governance, increased transparency, and integration of zakat data nationally. However, challenges still arise in the form of limited distribution coverage, delays in the distribution of funds, and lack of synergy between BAZNAS and local amil zakat institutions (LAZ). This condition has the potential to hinder the optimization of the impact of zakat on the economic development of the people in the region. Therefore, this article recommends an integrative model between BAZNAS and LAZ that prioritizes collaboration, operational decentralization, and local capacity building. The integration is expected to be able to increase the effectiveness of zakat management and strengthen its contribution to economic development based on social justice and community empowerment.